Implementasi Pembelajaran Akidah Akhlak dalam Pencegahan Kenakalan Remaja di MA Minhajut Thullab Sumberberas - Jon Iskandar Bahari (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study employed a descriptive qualitative approach. Data collection methods included structured interviews, non-participant observation, and documentation. The informants were the principal, the Islamic aqidah and akhlak (belief and moral) teacher, and students at MA Minhajut Thullab. Data analysis techniques included data collection, data reduction, data presentation, and conclusion drawing. Data validity was verified using data source triangulation. This research discusses how Akidah Akhlak learning is implemented to prevent juvenile delinquency at MA Minhajut Thullab Sumberberas in the 2024/2025 academic year. The study was conducted through observation, interviews, and documentation. The results show that Akidah Akhlak learning is designed with thorough planning, interactive implementation, and comprehensive evaluation focusing not only on students’ knowledge but also on their attitudes and behavior. Teachers apply approaches that relate to students’ daily lives, along with motivation and role-modeling. Supporting factors include the religious school environment and competent teachers. Meanwhile, obstacles include limited facilities and the diverse backgrounds of the students. Overall, Akidah Akhlak learning has proven effective in helping students develop discipline, respect, and avoid deviant behavior.